High-performance corrosion-resistant environment-friendly coating and preparation process thereof

By preparing high-performance corrosion-resistant environmentally friendly coatings, using specific chemical reactions to form flame-retardant polysiloxanes and aldehyde-based phosphonates, combined with epoxy resins and aluminum hydroxide fillers, the existing coatings are solved inadequate performance in the face of severe environmental corrosion and extreme environments, and the coating effect of high performance, durability and safety is achieved.

CN119875467AActive Publication Date: 2025-04-25HUACUI MICROMAG ELECTRONICS (JIANGSU) CO LTD

Patent Information

Application Number
CN202510041314.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-25
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

Existing paints are difficult to meet the needs of high performance, durability and safety when facing severe environmental corrosion, extreme environments and complex climate conditions.

Method used

By preparing a high-performance corrosion-resistant environmentally friendly coating, a series of reactions are carried out by using materials such as hexachlorocyclotriphosphazene, ethanolamine, gamma-glycidyl etheroxypropyltrimethoxysilane and NH2-POSS to form flame-retardant polysiloxane and aldehyde-based phosphonate, combined with epoxy resin and aluminum hydroxide filler to form composite silicone.

Benefits of technology

The coating significantly improves flame retardant performance, chemical stability, UV resistance and hydrophobic corrosion resistance, and can maintain stable performance in various harsh environments, extend the service life of equipment and facilities, and reduce maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, in particular to a high-performance corrosion-resistant environment-friendly coating and a preparation process thereof. The preparation method comprises the following steps: firstly, preparing flame-retardant polysiloxane and formylated phosphonate, and then reacting the formylated phosphonate with the flame-retardant polysiloxane in an alkaline environment to obtain the composite organic silicon. And finally mixing the epoxy resin, the composite organic silicon, the aluminum hydroxide filler and the like to obtain the finished coating. The finished coating prepared by the invention has good flame retardance, weather resistance and corrosion resistance, so that the coating has a wide application prospect in the technical field of coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a high-performance corrosion-resistant and environmentally friendly coating and a preparation process thereof. Background Art

[0002] In today's rapidly developing industrial and social environment, high-performance coatings play an indispensable role in many fields due to their excellent physical and chemical properties. First, high-performance coatings have important applications in the field of industrial corrosion protection, because modern industrial equipment and infrastructure, such as ships, bridges, pipelines and chemical equipment, are facing severe environmental corrosion challenges. Traditional anti-corrosion coatings often find it difficult to meet these needs, but high-performance coatings effectively extend the service life of these equipment and facilities and reduce maintenance costs with their excellent corrosion resistance, weather resistance and chemical resistance. Secondly, in the field of transportation, due to the extremely high requirements for appearance and performance of aviation, automobiles and rail transportation equipment, high-performance coatings have also demonstrated their unique value. This type of coating not only provides high-quality surface protection, but also enhances the safety and comfort of equipment. Specifically, aviation coatings need to have excellent weather resistance, heat resistance and UV resistance to ensure the safety and reliability of aircraft when flying at high altitudes; while automotive coatings need to have good wear resistance and chemical resistance to adapt to complex road environments. However, in certain extreme environments, such as fire, the coating may be directly exposed to dangerous factors such as high heat, flames and smoke, which can easily cause the combustion of combustibles or accelerate the spread of fire. Therefore, it is particularly important to develop coatings with strong flame retardant properties. Such coatings can better resist the erosion of these extreme environments, thereby reducing the risk of fire and protecting the safety of building structures and personnel. In addition, in the natural environment, coatings are long-term affected by complex climatic conditions such as sunlight, rain and temperature differences, which can easily cause the coating to age, fade and even peel off. Therefore, coatings with strong weather resistance are also highly respected. They can better resist the erosion of these natural factors, maintain the beauty and functionality of the coating, thereby extending its service life and reducing maintenance costs.

[0003] In order to overcome the defects of the prior art, the present invention provides a high-performance corrosion-resistant and environmentally friendly coating and a preparation process thereof. Summary of the invention

[0004] The purpose of the present invention is to provide a high-performance corrosion-resistant environmentally friendly coating and a preparation process thereof to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A preparation process of a high-performance corrosion-resistant and environmentally friendly coating comprises the following steps: Step 1: dissolve hexachlorocyclotriphosphazene in xylene, slowly add ethanolamine dropwise under a nitrogen environment, slowly heat up to 70-75°C, stir and reflux for reaction for 12-15h, wash, dry and remove impurities from the bottom liquid after the reaction to obtain hydroxylated cyclotriphosphazene; under a nitrogen environment, mix hydroxylated cyclotriphosphazene, γ-glycidyloxypropyltrimethoxysilane and catalyst stannous octoate, slowly heat up to 50-55°C and stir for reaction for 8-10h to obtain epoxidized cyclotriphosphazene; dissolve NH2-POSS in xylene, add epoxidized cyclotriphosphazene and ultrasonically disperse evenly, slowly heat up to 100-110°C and react for 2-3h to obtain flame-retardant polysiloxane; Step 2: In a nitrogen environment, tetrapentyl alcohol and trichlorophosphorus are mixed, heated to 90-95°C for reaction for 1.0-1.5h, then heated to 140-150°C for reaction for 7-9h, and then heated to 160-170°C for reaction for 1.0-1.5h. After the reaction is completed, the mixture is cooled, extracted, filtered, spin-dried, and vacuum-dried to obtain a hydroxylated phosphonate; the hydroxylated phosphonate, p-formylbenzoic acid, and 4-dimethylaminopyridine are dissolved in anhydrous dichloromethane, and N, N-diisopropylcarbodiimide is added for reaction for 10-14h. After the reaction is completed, the mixture is washed with a saturated sodium bicarbonate solution, a saturated sodium chloride solution, and deionized water, and then dried and solvent removed to obtain an aldehyded phosphonate; Step 3: dissolve the formaldehyde phosphonate and flame retardant polysiloxane in toluene, add Tris buffer, react at 80-90°C for 5-7h, cool to room temperature after the reaction, remove the lower precipitate, centrifuge, and vacuum dry to obtain a composite silicone; mix the epoxy resin and xylene evenly, add the composite silicone, aluminum hydroxide filler, dispersant, and leveling agent, fully ball-mill, and then add polyamide 651 curing agent to obtain the finished product.

[0006] More optimally, in step 1, when preparing hydroxylated cyclotriphosphazene, the reaction molar ratio of hexachlorocyclotriphosphazene and ethanolamine is 1:(5-6).

[0007] More optimally, in step 1, when preparing epoxidized cyclotriphosphazene, the reaction molar ratio of hydroxylated cyclotriphosphazene and γ-glycidyloxypropyltrimethoxysilane is 1:(5-6).

[0008] More optimally, in step 1, when preparing flame-retardant polysiloxane, the reaction molar ratio of NH2-POSS and epoxidized cyclotriphosphazene is 1:(4-5).

[0009] More optimally, the preparation process of NH2-POSS is as follows: dissolve tetraethylammonium hydroxide in a mixed solvent, then slowly add 3-aminopropyltriethoxysilane, stir and react at 60-70°C for 20-25h, and after the reaction is completed, cool at room temperature, precipitate at low temperature, filter, and vacuum dry to obtain NH2-POSS; the mixed solvent includes deionized water, propanol, and acetonitrile in a volume ratio of 1:0.4:0.1; the reaction volume ratio of tetraethylammonium hydroxide and 3-aminopropyltriethoxysilane is 0.5:(55-60).

[0010] More optimally, in step 2, when preparing the hydroxylated phosphonate, the reaction molar ratio of tetrapentanol and phosphorus trichloride is 1:(1.0-1.2).

[0011] More optimally, in step 2, when preparing the formyl phosphonate, the reaction molar ratio of the hydroxyl group in the hydroxyl phosphonate and the carboxyl group in the p-formylbenzoic acid is 1:(3-4).

[0012] More optimally, in step three, tris(hydroxymethyl)aminomethane hydrochloride is dissolved in deionized water, and then the pH is adjusted to 8.5-9.0 using sodium hydroxide solution to obtain 0.5-0.6 g / mL Tris buffer.

[0013] More optimally, in step three, when preparing the composite organosilicon, the reaction molar ratio of the aldehyde group in the formaldehyde-phosphonic acid ester and the amino group in the flame-retardant polysiloxane is (1.3-1.5):1.

[0014] More optimally, in step three, the contents of the components of the epoxy coating are: by mass, 50-60 parts of epoxy resin, 25-30 parts of xylene, 13-18 parts of composite silicone, 8-10 parts of aluminum hydroxide filler, 1-2 parts of dispersant, 1-2 parts of leveling agent, and 25-30 parts of polyamide 651 curing agent.

[0015] Beneficial effects of the present invention: The present invention is characterized in that, in step one, by adding hexachlorocyclotriphosphazene and ethanolamine, a substitution reaction occurs to obtain hydroxylated cyclotriphosphazene. Further, by adding hydroxylated cyclotriphosphazene, γ-glycidyloxypropyltrimethoxysilane, and catalyst stannous octoate, a hydrolysis condensation reaction occurs, and finally epoxidized cyclotriphosphazene is prepared. Epoxidized cyclotriphosphazene is then added to the NH2-POSS solution, a nucleophilic ring-opening reaction occurs, and the epoxidized cyclotriphosphazene with a variety of flame-retardant components is grafted to the surface of the caged amino polysiloxane to obtain a flame-retardant polysiloxane. In this step, the caged amino polysiloxane is used as the core, and a flame-retardant structure containing silicon, nitrogen, and phosphorus is further grafted on the surface to obtain a flame-retardant polysiloxane. Among them, the large amount of silicon element introduced improves the UV resistance of the material, and the siloxane group in the composite organosilicon can absorb and scatter ultraviolet rays, reduce the aging effect of ultraviolet rays on the material, and improve the weather resistance of the material. In addition, the siloxane group has excellent chemical stability and can effectively resist erosion by environmental factors such as moisture, allowing it to maintain stable performance in various harsh environments.

[0016] The present invention is characterized in that, in step 2 and step 3, by adding tetrapentyl alcohol and trichlorothiophosphorus, a substitution reaction occurs to obtain a hydroxylated phosphonate; further, by adding a hydroxylated phosphonate, p-formylbenzoic acid, 4-dimethylaminopyridine, and N, N-diisopropylcarbodiimide, an esterification reaction occurs to obtain an aldehyded phosphonate. In step 3, the aldehyded phosphonate prepared in step 2 and the remaining amino groups in the flame-retardant polysiloxane undergo a Schiff base reaction, and the phosphonate structure is also grafted to the surface of the caged amino polysiloxane, and finally a composite organosilicon is obtained. Among them, in step 1, by controlling the reaction molar ratio of NH2-POSS and epoxidized cyclotriphosphazene to be 1: (4-5), the epoxidized cyclotriphosphazene can be grafted to the surface of NH2-POSS, and part of the amino groups can be retained to participate in the Schiff base reaction in step 3, thereby ensuring the introduction of a phosphonate structure with good flame retardancy. In addition, the surface of epoxidized cyclotriphosphazene has multiple epoxy groups. When the reaction molar ratio of NH2-POSS to epoxidized cyclotriphosphazene is 1: (4-5), there will be more epoxy groups remaining. Therefore, after adding the polyamide 651 curing agent in step three, the composite silicone prepared by the present invention and the main resin epoxy resin will be fully compatible and undergo chemical cross-linking reactions, forming a more stable cross-linking structure together with the main resin epoxy resin, thereby optimizing the comprehensive performance of the material.

[0017] In summary, the composite organosilicon prepared by the present invention integrates three elements with excellent flame retardant properties: silicon, nitrogen, and phosphorus. Silicon can form a glassy protective layer during combustion to delay combustion; nitrogen can release nitrogen during combustion to dilute combustible gases and inhibit combustion; phosphorus can promote the carbonization process at high temperatures to form a protective carbon layer to isolate oxygen; through the synergistic effect of these elements, the flame retardant properties are significantly improved, making the coating perform better in fires. In addition, by introducing structures such as siloxane, the chemical stability, UV resistance, and hydrophobic corrosion resistance of the finished coating can be significantly improved, thereby ensuring that the product maintains stable performance in various harsh environments. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Source of raw materials: Epoxy resin, provided by Langfang Yushi Anticorrosion Materials Co., Ltd., model 6101; dispersant, provided by Shenzhen Longdi Chemical Co., Ltd., model BYK-2070; leveling agent, provided by BYK Chemical Technology Consulting Co., Ltd., specifically leveling agent BYD-354, specification is industrial grade; polyamide 651 curing agent, provided by Beijing Xiangshan United Additive Factory, specification is industrial grade; in terms of mass parts, one part is 1g.

[0020] Example 1: Step 1: dissolve tetraethylammonium hydroxide in a mixed solvent, then slowly drop 3-aminopropyltriethoxysilane, stir and react at 70°C for 25h, and after the reaction is completed, cool at room temperature, precipitate at low temperature, filter, and vacuum dry to obtain NH2-POSS; the mixed solvent includes deionized water, propanol, and acetonitrile in a volume ratio of 1:0.4:0.1; the reaction volume ratio of tetraethylammonium hydroxide and 3-aminopropyltriethoxysilane is 0.5:57; Dissolve hexachlorocyclotriphosphazene in xylene, slowly add ethanolamine in a nitrogen environment, slowly heat up to 75°C, stir and reflux for 15 hours, wash, dry and remove impurities from the bottom liquid after the reaction to obtain hydroxylated cyclotriphosphazene; mix hydroxylated cyclotriphosphazene, γ-glycidyloxypropyltrimethoxysilane and catalyst stannous octoate in a nitrogen environment, slowly heat up to 55°C and stir for 10 hours to obtain epoxidized cyclotriphosphazene; dissolve NH2-POSS in xylene , then add epoxidized cyclotriphosphazene and disperse it evenly by ultrasonication, slowly heat up to 110°C and react for 3h to obtain flame-retardant polysiloxane; when preparing hydroxylated cyclotriphosphazene, the reaction molar ratio of hexachlorocyclotriphosphazene and ethanolamine is 1:5.5; when preparing epoxidized cyclotriphosphazene, the reaction molar ratio of hydroxylated cyclotriphosphazene and γ-glycidyloxypropyltrimethoxysilane is 1:5.5; when preparing flame-retardant polysiloxane, the reaction molar ratio of NH2-POSS and epoxidized cyclotriphosphazene is 1:4.5; Step 2: In a nitrogen environment, tetrapentyl alcohol and trichlorothiophosphorus are mixed, heated to 95°C for reaction for 1.5h, then heated to 150°C for reaction for 9h, and then heated to 170°C for reaction for 1.5h. After the reaction, the mixture is cooled, extracted, filtered, spin-dried, and vacuum dried to obtain a hydroxylated phosphonate. The hydroxylated phosphonate, p-formylbenzoic acid, and 4-dimethylaminopyridine are dissolved in anhydrous dichloromethane, and N, N-diisopropylcarbodiimide is added for reaction for 14h. After the reaction, the mixture is washed with a saturated sodium bicarbonate solution, a saturated sodium chloride solution, and deionized water, and then dried and solvent removed to obtain an aldehyded phosphonate. When preparing the hydroxylated phosphonate, the reaction molar ratio of tetrapentyl alcohol and trichlorothiophosphorus is 1:1. When preparing the aldehyded phosphonate, the reaction molar ratio of the hydroxyl group in the hydroxylated phosphonate and the carboxyl group in the p-formylbenzoic acid is 1:3.5. Step 3: Dissolve tris(hydroxymethyl)aminomethane hydrochloride in deionized water, and then adjust the pH to 8.5 with sodium hydroxide solution to obtain 0.5 g / mL Tris buffer; The aldehyded phosphonate and flame retardant polysiloxane were dissolved in toluene, and Tris buffer was added, and the reaction was carried out at 90°C for 7 hours. After the reaction was completed, the reaction was cooled to room temperature, the lower precipitate was centrifuged and vacuum dried to obtain a composite silicone. 50g of epoxy resin and 25g of xylene were mixed evenly, and 15g of composite silicone, 8g of aluminum hydroxide filler, 1g of dispersant and 1g of leveling agent were added. After sufficient ball milling, 25g of polyamide 651 curing agent was added to obtain the finished product. When preparing the composite silicone, the reaction molar ratio of the aldehyde group in the aldehyded phosphonate and the amino group in the flame retardant polysiloxane was 1.4:1.

[0021] Example 2: Step 1: dissolve tetraethylammonium hydroxide in a mixed solvent, then slowly drop 3-aminopropyltriethoxysilane, stir and react at 65°C for 23h, and after the reaction is completed, cool at room temperature, precipitate at low temperature, filter, and vacuum dry to obtain NH2-POSS; the mixed solvent includes deionized water, propanol, and acetonitrile in a volume ratio of 1:0.4:0.1; the reaction volume ratio of tetraethylammonium hydroxide and 3-aminopropyltriethoxysilane is 0.5:57; Dissolve hexachlorocyclotriphosphazene in xylene, slowly add ethanolamine in a nitrogen environment, slowly heat up to 73°C, stir and reflux for 14 hours, wash, dry and remove impurities from the bottom liquid after the reaction to obtain hydroxylated cyclotriphosphazene; mix hydroxylated cyclotriphosphazene, γ-glycidyloxypropyltrimethoxysilane and catalyst stannous octoate in a nitrogen environment, slowly heat up to 53°C and stir for 9 hours to obtain epoxidized cyclotriphosphazene; dissolve NH2-POSS in xylene, Then add epoxidized cyclotriphosphazene and disperse it evenly by ultrasonication, slowly heat up to 105°C and react for 2.5h to obtain flame-retardant polysiloxane; when preparing hydroxylated cyclotriphosphazene, the reaction molar ratio of hexachlorocyclotriphosphazene and ethanolamine is 1:5.5; when preparing epoxidized cyclotriphosphazene, the reaction molar ratio of hydroxylated cyclotriphosphazene and γ-glycidyloxypropyltrimethoxysilane is 1:5.5; when preparing flame-retardant polysiloxane, the reaction molar ratio of NH2-POSS and epoxidized cyclotriphosphazene is 1:4.5; Step 2: In a nitrogen environment, tetrapentyl alcohol and trichlorothiophosphorus are mixed, heated to 93°C for reaction for 1.2h, then heated to 145°C for reaction for 8h, and then heated to 165°C for reaction for 1.3h. After the reaction, the mixture is cooled, extracted, filtered, spin-dried, and vacuum dried to obtain a hydroxylated phosphonate. The hydroxylated phosphonate, p-formylbenzoic acid, and 4-dimethylaminopyridine are dissolved in anhydrous dichloromethane, and N, N-diisopropylcarbodiimide is added for reaction for 12h. After the reaction, the mixture is washed with a saturated sodium bicarbonate solution, a saturated sodium chloride solution, and deionized water, and then dried and solvent removed to obtain an aldehyded phosphonate. When preparing the hydroxylated phosphonate, the reaction molar ratio of tetrapentyl alcohol and trichlorothiophosphorus is 1:1. When preparing the aldehyded phosphonate, the reaction molar ratio of the hydroxyl group in the hydroxylated phosphonate and the carboxyl group in the p-formylbenzoic acid is 1:3.5. Step 3: Dissolve tris(hydroxymethyl)aminomethane hydrochloride in deionized water, and then adjust the pH to 8.5 with sodium hydroxide solution to obtain 0.5 g / mL Tris buffer; The aldehyded phosphonate and flame retardant polysiloxane were dissolved in toluene, and Tris buffer was added, and the reaction was carried out at 85°C for 6 hours. After the reaction was completed, the reaction was cooled to room temperature, the lower precipitate was centrifuged and vacuum dried to obtain a composite silicone. 50g of epoxy resin and 25g of xylene were mixed evenly, and 15g of composite silicone, 8g of aluminum hydroxide filler, 1g of dispersant, and 1g of leveling agent were added. After sufficient ball milling, 25g of polyamide 651 curing agent was added to obtain the finished product. When preparing the composite silicone, the reaction molar ratio of the aldehyde group in the aldehyded phosphonate and the amino group in the flame retardant polysiloxane was 1.4:1.

[0022] Example 3: Step 1: dissolving tetraethylammonium hydroxide in a mixed solvent, then slowly adding 3-aminopropyltriethoxysilane, stirring and reacting at 60°C for 20 hours, cooling at room temperature after the reaction, precipitating at low temperature, filtering, and vacuum drying to obtain NH2-POSS; the mixed solvent includes deionized water, propanol, and acetonitrile in a volume ratio of 1:0.4:0.1; the reaction volume ratio of tetraethylammonium hydroxide and 3-aminopropyltriethoxysilane is 0.5:57; Dissolve hexachlorocyclotriphosphazene in xylene, slowly add ethanolamine in a nitrogen environment, slowly heat up to 70°C, stir and reflux for 12 hours, wash, dry and remove impurities from the bottom liquid after the reaction to obtain hydroxylated cyclotriphosphazene; mix hydroxylated cyclotriphosphazene, γ-glycidyloxypropyltrimethoxysilane and catalyst stannous octoate in a nitrogen environment, slowly heat up to 50°C and stir for 8 hours to obtain epoxidized cyclotriphosphazene; dissolve NH2-POSS in xylene , then add epoxidized cyclotriphosphazene and disperse it evenly by ultrasonication, slowly heat up to 100℃ and react for 2h to obtain flame-retardant polysiloxane; when preparing hydroxylated cyclotriphosphazene, the reaction molar ratio of hexachlorocyclotriphosphazene and ethanolamine is 1:5.5; when preparing epoxidized cyclotriphosphazene, the reaction molar ratio of hydroxylated cyclotriphosphazene and γ-glycidyloxypropyltrimethoxysilane is 1:5.5; when preparing flame-retardant polysiloxane, the reaction molar ratio of NH2-POSS and epoxidized cyclotriphosphazene is 1:4.5; Step 2: In a nitrogen environment, tetrapentyl alcohol and trichlorothiophosphorus are mixed, heated to 90°C for reaction for 1.0h, then heated to 140°C for reaction for 7h, and then heated to 160°C for reaction for 1.0h. After the reaction, the mixture is cooled, extracted, filtered, spin-dried, and vacuum dried to obtain a hydroxylated phosphonate. The hydroxylated phosphonate, p-formylbenzoic acid, and 4-dimethylaminopyridine are dissolved in anhydrous dichloromethane, and N, N-diisopropylcarbodiimide is added for reaction for 10h. After the reaction, the mixture is washed with a saturated sodium bicarbonate solution, a saturated sodium chloride solution, and deionized water, and then dried and solvent removed to obtain an aldehyded phosphonate. When preparing the hydroxylated phosphonate, the reaction molar ratio of tetrapentyl alcohol and trichlorothiophosphorus is 1:1. When preparing the aldehyded phosphonate, the reaction molar ratio of the hydroxyl group in the hydroxylated phosphonate and the carboxyl group in the p-formylbenzoic acid is 1:3.5. Step 3: Dissolve tris(hydroxymethyl)aminomethane hydrochloride in deionized water, and then adjust the pH to 8.5 with sodium hydroxide solution to obtain 0.5 g / mL Tris buffer; The aldehyded phosphonate and flame retardant polysiloxane were dissolved in toluene, and Tris buffer was added, and the reaction was carried out at 80°C for 5 hours. After the reaction was completed, the reaction was cooled to room temperature, the lower precipitate was centrifuged and vacuum dried to obtain a composite silicone. 50g of epoxy resin and 25g of xylene were mixed evenly, and 15g of composite silicone, 8g of aluminum hydroxide filler, 1g of dispersant and 1g of leveling agent were added. After sufficient ball milling, 25g of polyamide 651 curing agent was added to obtain the finished product. When preparing the composite silicone, the reaction molar ratio of the aldehyde group in the aldehyded phosphonate and the amino group in the flame retardant polysiloxane was 1.4:1.

[0023] Comparative Example 1: Remove step 1: preparation of flame retardant polysiloxane, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: In a nitrogen environment, tetrapentanol and trichlorophosphorus are mixed, heated to 93°C for reaction for 1.2h, then heated to 145°C for reaction for 8h, and then heated to 165°C for reaction for 1.3h. After the reaction, cool, extract, filter, spin dry, and vacuum dry to obtain hydroxylated phosphonate; dissolve hydroxylated phosphonate, p-formylbenzoic acid, and 4-dimethylaminopyridine in anhydrous dichloromethane, and then add N, The reaction was carried out with N-diisopropylcarbodiimide for 14 hours, and after the reaction, the mixture was washed with a saturated sodium bicarbonate solution, a saturated sodium chloride solution, deionized water, dried, and the solvent was removed to obtain an aldehyded phosphonate. When preparing the hydroxylated phosphonate, the reaction molar ratio of tetrapentyl alcohol and trichlorothiophosphorus was 1:1. When preparing the aldehyded phosphonate, the reaction molar ratio of the hydroxyl group in the hydroxylated phosphonate and the carboxyl group in the p-aldehyde benzoic acid was 1:3.5. Step 2: Evenly mix 50g of epoxy resin and 25g of xylene, then add 15g of formaldehyde phosphonate, 8g of aluminum hydroxide filler, 1g of dispersant, and 1g of leveling agent, and after sufficient ball milling, add 25g of polyamide 651 curing agent to obtain the finished product.

[0024] Comparative Example 2: Step 2: Preparation of aldehyde-phosphonic acid ester is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: Dissolve tetraethylammonium hydroxide in a mixed solvent, and then slowly drop 3-aminopropyltriethoxysilane, stir and react at 70°C for 25h, and after the reaction is completed, cool at room temperature, precipitate at low temperature, filter, and vacuum dry to obtain NH2-POSS; the mixed solvent includes deionized water, propanol, and acetonitrile in a volume ratio of 1:0.4:0.1; the reaction volume ratio of tetraethylammonium hydroxide and 3-aminopropyltriethoxysilane is 0.5:57; Dissolve hexachlorocyclotriphosphazene in xylene, slowly add ethanolamine in a nitrogen environment, slowly heat up to 75°C, stir and reflux for 15 hours, wash, dry and remove impurities from the bottom liquid after the reaction to obtain hydroxylated cyclotriphosphazene; mix hydroxylated cyclotriphosphazene, γ-glycidyloxypropyltrimethoxysilane and catalyst stannous octoate in a nitrogen environment, slowly heat up to 55°C and stir for 10 hours to obtain epoxidized cyclotriphosphazene; dissolve NH2-POSS in xylene , then add epoxidized cyclotriphosphazene and disperse it evenly by ultrasonication, slowly heat up to 110°C and react for 3h to obtain flame-retardant polysiloxane; when preparing hydroxylated cyclotriphosphazene, the reaction molar ratio of hexachlorocyclotriphosphazene and ethanolamine is 1:5.5; when preparing epoxidized cyclotriphosphazene, the reaction molar ratio of hydroxylated cyclotriphosphazene and γ-glycidyloxypropyltrimethoxysilane is 1:5.5; when preparing flame-retardant polysiloxane, the reaction molar ratio of NH2-POSS and epoxidized cyclotriphosphazene is 1:4.5; Step 2: Evenly mix 50g of epoxy resin and 25g of xylene, then add 15g of flame retardant polysiloxane, 8g of aluminum hydroxide filler, 1g of dispersant, and 1g of leveling agent, and after sufficient ball milling, add 25g of polyamide 651 curing agent to obtain the finished product.

[0025] Comparative Example 3: The preparation of the composite silicone is removed, and the rest is the same as Example 1. The specific steps are as follows: Step 1: Mix 50g of epoxy resin and 25g of xylene evenly, then add 8g of aluminum hydroxide filler, 1g of dispersant, and 1g of leveling agent, and after sufficient ball milling, add 25g of polyamide 651 curing agent to obtain the finished product.

[0026] Flame retardancy test: The finished coating prepared by the present invention is applied to the surface of a substrate as a sample, and the flame retardancy is tested according to the UL-94 vertical burning test standard.

[0027] Weather resistance test: The finished coating prepared by the present invention is applied to the surface of a substrate as a sample, and the weather resistance of the sample is tested according to ASTM G154 standard. The test time is 850 hours, and the surface of the sample is observed to determine the weather resistance of the sample.

[0028] Contact angle test: The finished coating prepared by the present invention is applied to the surface of the substrate as a sample, and the contact angle between the sample surface and water is measured using a contact angle tester of Guangdong Dainte Intelligent Technology Co., Ltd. to determine the hydrophobicity of the sample surface. The results are as follows:

[0029] Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. From the experimental data, it can be seen that the various properties of the samples have no obvious fluctuations.

[0030] Comparative Example 1: Step 1: Preparation of flame-retardant polysiloxane is removed, and the rest is the same as Example 1. It can be seen from the experimental data that, compared with Example 1, the flame retardant grade becomes V-1, and the UV aging resistance effect is powdering and discoloration in many places on the surface of the sample, and the contact angle is reduced to 86°. The reasons are analyzed as follows: the flame-retardant polysiloxane prepared by the present invention can significantly improve the flame retardant properties through the synergistic effect of multiple flame retardant elements; the large amount of siloxane structures in the flame retardant polysiloxane can effectively resist the erosion of environmental factors such as humidity and heat due to its excellent chemical stability, and at the same time significantly improve the hydrophobicity of the sample surface; therefore, after the preparation of the flame retardant polysiloxane is removed, the flame retardancy is reduced, the weather resistance is reduced, and the hydrophobicity is reduced.

[0031] Comparative Example 2: Step 2: Preparation of formaldehyded phosphonate is removed, and the rest is the same as Example 1. It can be seen from the experimental data that the flame retardancy level becomes V-1 compared with Example 1. The reason is analyzed as follows: the formaldehyded phosphonate contains a phosphonate flame retardant structure, which can decompose at high temperature and form low-volatile phosphorus oxides, promoting the formation of a stable carbonized layer on the surface of the material to prevent the spread of flames; therefore, after the preparation of formaldehyded phosphonate is removed, the flame retardancy is reduced.

[0032] Comparative Example 3: The preparation of the composite silicone is removed, and the rest is the same as Example 1. It can be seen from the experimental data that, compared with Example 1, the flame retardant grade becomes V-2, and the UV aging resistance effect is that the surface of the sample is severely powdered and obviously discolored, and the contact angle is reduced to 81°. The reason is analyzed as follows: the composite silicone is prepared by reacting a flame retardant polysiloxane and an aldehyded phosphonate, so the material can combine the properties of the two materials to obtain a composite silicone material with good flame retardancy, weather resistance and hydrophobicity; therefore, after removing the preparation of the composite silicone, the flame retardancy is reduced, the weather resistance is reduced, and the hydrophobicity is reduced.

[0033] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0034] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A preparation process of a high-performance corrosion-resistant and environmentally friendly coating, characterized in that: The following steps are involved: Step 1: dissolve hexachlorocyclotriphosphazene in xylene, slowly add ethanolamine dropwise under a nitrogen environment, slowly heat up to 70-75°C, stir and reflux for reaction for 12-15h, wash, dry and remove impurities from the bottom liquid after the reaction to obtain hydroxylated cyclotriphosphazene; under a nitrogen environment, mix hydroxylated cyclotriphosphazene, γ-glycidyloxypropyltrimethoxysilane and catalyst stannous octoate, slowly heat up to 50-55°C and stir for reaction for 8-10h to obtain epoxidized cyclotriphosphazene; dissolve NH2-POSS in xylene, add epoxidized cyclotriphosphazene and ultrasonically disperse evenly, slowly heat up to 100-110°C and react for 2-3h to obtain flame-retardant polysiloxane; Step 2: In a nitrogen environment, tetrapentyl alcohol and trichlorophosphorus are mixed, heated to 90-95°C for reaction for 1.0-1.5h, then heated to 140-150°C for reaction for 7-9h, and then heated to 160-170°C for reaction for 1.0-1.5h. After the reaction is completed, the mixture is cooled, extracted, filtered, spin-dried, and vacuum-dried to obtain a hydroxylated phosphonate; the hydroxylated phosphonate, p-formylbenzoic acid, and 4-dimethylaminopyridine are dissolved in anhydrous dichloromethane, and N, N-diisopropylcarbodiimide is added for reaction for 10-14h. After the reaction is completed, the mixture is washed with a saturated sodium bicarbonate solution, a saturated sodium chloride solution, and deionized water, and then dried and solvent removed to obtain an aldehyded phosphonate; Step 3: dissolve the formaldehyde phosphonate and flame retardant polysiloxane in toluene, add Tris buffer, react at 80-90°C for 5-7h, cool to room temperature after the reaction, remove the lower precipitate, centrifuge, and vacuum dry to obtain a composite silicone; mix the epoxy resin and xylene evenly, add the composite silicone, aluminum hydroxide filler, dispersant, and leveling agent, fully ball-mill, and then add polyamide 651 curing agent to obtain the finished product.

2. The preparation process of a high-performance corrosion-resistant and environmentally friendly coating according to claim 1, characterized in that: In step 1, when preparing hydroxylated cyclotriphosphazene, the reaction molar ratio of hexachlorocyclotriphosphazene and ethanolamine is 1:(5-6).

3. The preparation process of a high-performance corrosion-resistant and environmentally friendly coating according to claim 1 is characterized in that: In step 1, when preparing epoxidized cyclotriphosphazene, the reaction molar ratio of hydroxylated cyclotriphosphazene and γ-glycidyloxypropyltrimethoxysilane is 1:(5-6).

4. The preparation process of a high-performance corrosion-resistant and environmentally friendly coating according to claim 1 is characterized in that: In step 1, when preparing the flame retardant polysiloxane, the reaction molar ratio of NH2-POSS and epoxidized cyclotriphosphazene is 1:(4-5).

5. The preparation process of a high-performance corrosion-resistant and environmentally friendly coating according to claim 4 is characterized in that: The preparation process of NH2-POSS is as follows: dissolving tetraethylammonium hydroxide in a mixed solvent, then slowly adding 3-aminopropyltriethoxysilane, stirring and reacting at 60-70°C for 20-25h, cooling at room temperature after the reaction, precipitating at low temperature, filtering, and vacuum drying to obtain NH2-POSS; the mixed solvent includes deionized water, propanol, and acetonitrile in a volume ratio of 1:0.4:0.1; the reaction volume ratio of tetraethylammonium hydroxide and 3-aminopropyltriethoxysilane is 0.5:(55-60).

6. The preparation process of a high-performance corrosion-resistant and environmentally friendly coating according to claim 1, characterized in that: When preparing hydroxylated phosphonic acid esters, the reaction molar ratio of tetrapentanol and phosphorus trichloride is 1:(1.0-1.2).

7. The preparation process of a high-performance corrosion-resistant and environmentally friendly coating according to claim 1, characterized in that: In step 2, when preparing the formyl phosphonate, the reaction molar ratio of the hydroxyl group in the hydroxyl phosphonate and the carboxyl group in the p-formylbenzoic acid is 1:(3-4).

8. The process for preparing a high-performance corrosion-resistant and environmentally friendly coating according to claim 1, characterized in that: In step 3, tris(hydroxymethyl)aminomethane hydrochloride is dissolved in deionized water, and then the pH is adjusted to 8.5-9.0 using sodium hydroxide solution to obtain 0.5-0.6 g / mL Tris buffer.

9. The process for preparing a high-performance corrosion-resistant and environmentally friendly coating according to claim 1, characterized in that: In step 3, when preparing the composite organosilicon, the reaction molar ratio of the aldehyde group in the aldehyde-formylated phosphonate and the amino group in the flame-retardant polysiloxane is (1.3-1.5):

1.

10. The preparation process of a high-performance corrosion-resistant and environmentally friendly coating according to claim 1, characterized in that: In step three, the contents of the components of the epoxy coating are: by mass, 50-60 parts of epoxy resin, 25-30 parts of xylene, 13-18 parts of composite silicone, 8-10 parts of aluminum hydroxide filler, 1-2 parts of dispersant, 1-2 parts of leveling agent, and 25-30 parts of polyamide 651 curing agent.

Citation Information

Patent Citations

  • Octa-aminopropyl cage type sesquialter siloxane and preparation thereof

    CN101503419A

  • Siloxane-modified cyclotriphosphazene halogen-free flame retardant and preparation method and application thereof

    CN107964117A

  • Sulfur containing cage-like organic phosphate / ammonium polyphosphate compounded polyolefin fire retardant and preparation method thereof

    CN110804208A

  • Graphene oxide-based phosphorus-nitrogen-silicon composite flame-retardant copolyester and preparation method thereof

    CN115246927A

  • Pmsm control method

    KR102817326B1

Cited By

  • Flame-retardant corrosion-resistant coating and preparation method thereof

    CN121450202A

  • A fire-retardant corrosion-resistant coating and a method for preparing the same

    CN121450202B